THE SOMATIC CULTURAL CODES IN THE STUDY OF ENGLISH, RUSSIAN AND UZBEK PHRASEOLOGISMS - Batyrkhanova, Madina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article is devoted to the study of somatic phraseological units, which allows us to identify their main factors in the Uzbek, Russian and English languages. Linguists and researchers have studied the cultural codes in phraseology and highlighted their various classifications. The issue of categorizing phraseology into cultural codes plays an important role in revealing the national landscape of the world. FBs belonging to one of the cultural codes can also be related to other cultural codes, thus revealing the integrity and hierarchy, i.e., gradation, inherent in the semiotic system of language. This research paper focuses on the issues related to somatic phraseology in Uzbek, English and other cultural codes in Russian, identifying their equivalents and providing appropriate translation. The purpose of this paper is to study somatic units and identify their similarities and differences in Uzbek, Russian and English. A distinctive feature of somatic phraseology is the presence of many similarities in the figurative orientation of collocations in the languages. This feature sharply distinguishes SPhU from other thematic groups. The use of names of body parts in PhU is explained by the fact that when naming a new object, a person, first of all, relies on the association with what he knows and is familiar with. First of all, a person compares himself/herself with himself/herself, and his/her body parts with the things that surround him/her. Studying and comparing PhUs of two or more languages helps to reveal specific features of culture and mentality of different peoples. Sometimes it is possible to identify differences in the thinking of speakers of a particular language. Our study also revealed historical parallels characteristic of the languages being compared.